Role of PTH1R Signaling in Prx1+ Mesenchymal Progenitors during Eruption. (October 2020) - Cui, C.; Bi, R.; Liu, W.; Guan, S.; Li, P.; Song, D.; Xu, R.; Zheng, L.; Yuan, Q.; Zhou, X.; Fan, Y.
Tooth eruption is a complex process requiring precise interaction between teeth and adjacent tissues. Molecular analysis demonstrates that bone remodeling plays an essential role during eruption, suggesting that a parathyroid hormone 1 receptor (PTH1R) gene mutation is associated with disturbances in bone remodeling and results in primary failure of eruption (PFE). Recent research reveals the function of PTH1R signaling in mesenchymal progenitors, whereas the function of PTH1R in mesenchymal stem cells during tooth eruption remains incompletely understood. We investigated the specific role of PTH1R in Prx1 + progenitor expression during eruption. We found that Prx1 + -progenitors occur in mesenchymal stem cells residing in alveolar bone marrow surrounding incisors, at the base of molars and in the dental follicle and pulp of incisors. Mice with conditional deletion of PTH1R using the Prx1 promoter exhibited arrested mandibular incisor eruption and delayed molar eruption. Micro–computed tomography, histomorphometry, and molecular analyses revealed that mutant mice had significantly reduced alveolar bone formation concomitant with downregulated gene expression of key regulators of osteogenesis in PTH1R-deficient cells. Moreover, culturing orofacial bone-marrow-derived mesenchymal stem cells (OMSCs) from Prx1Cre;PTH1R fl/fl mice or from transfecting Cre recombinase adenovirus in OMSCs from PTH1R fl/fl mice suggested that lack of Pth1r expression inhibited osteogenic differentiation in vitro. However, bone resorption was not affected by PTH1R ablation, indicating the observed reduced alveolar bone volume was mainly due to impaired bone formation. Furthermore, we found irregular periodontal ligaments and reduced Periostin expression in mutant incisors, implying loss of PTH1R results in aberrant differentiation of periodontal ligament cells. Collectively, these data suggest that PTH1R signaling in Prx1 + progenitors plays a critical role in alveolar bone formation and periodontal ligament development during eruption. These findings have implications for our understanding of the physiologic and pathologic function of PTH1R signaling in tooth eruption and the progression of PFE.